Diffusion-transport properties of hydrogel membranes based on copolymers of 2-hydroxyethyl methacrylate with polyvinylpyrrolidone - Melnyk, Yuriy; Tsvyk, Volodymyr; Skorokhoda, Taras (Видавництво Львівської політехніки, 2017)
The results of researches of dialysis permeability hydrogel films on the basis of copolymers of 2-hydroxyethyl methacrylate with polyvinylpyrrolidone dependently on their composition and modes of dialysis have been carried out. Possibility of synthesized hydrogels applying as the diffusion dialysis membranes has been confirmed.
Keywords: hydrogel; copolymer; polyvinylpyrrolidone; films membranes; dialyze; permeability